Respiratory symptoms, immunological responses, and aeroallergen concentrations at a sawmill. - Halpin, D; Graneek, B; Lacey, J; Nieuwenhuijsen, M; Williamson, P; Venables, K; Newman Taylor, A (1994)
After identification of a case of extrinsic allergic alveolitis due to exposure to wood dust at a sawmill, all employees at the sawmill where he worked were studied with an occupational, environmental, and symptom questionnaire, spirometry, skin prick tests, and serum specific IgG measurements. Ninety five of current and 14 of 17 ex-sawmill workers were studied. As a basis for comparison, a group of 58 workers from a nearby light engineering factory were also studied. Few women (6) were employed and they were excluded from the analysis. Workers at the sawmill were stratified into high and low exposure groups depending on their place of work. This division was supported both by their subjective assessment of the dustiness of their environment and the results of personal dust samples. There were no significant differences between the three groups in age, height, smoking habits, exposure to other causes of extrinsic allergic alveolitis, forced expiratory volume in one second, forced vital capacity, atopic state, or cutaneous reactivity to moulds. In the high exposure group the prevalence of work related cough and nasal and eye symptoms was higher than in the low exposure and comparison groups. The prevalence of work related wheeze was similar in both the high exposure and comparison groups, but was lower in the low exposure group. The prevalences of chronic bronchitis and symptomatic bronchial hyper-reactivity were similar in the high and low exposure groups but were lower in the comparison group. Serum concentrations of specific IgG against extracts of sawdust and Trichoderma koningii were significantly higher in the high exposure group than in the other two groups. The prevalence of symptoms suggestive of extrinsic allergic alveolitis was 4.4% in the high exposure group, greater than in the low exposure group (0%), and the comparison group (1.9%). In conclusion extrinsic allergic alveolitis probably occurs in British sawmills, and among the exposed population its prevalence may be as high as that reported in Sweden. The allergen responsible is likely to be from mould growing on the wood and may be from Trichoderma koningii.